(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the efficacy of preventing hypothermia using active forced-air warming methods during open abdominal surgery lasting over 120 minutes under general anesthesia. Subject and methods: A cross-sectional descriptive study was conducted on 100 patients, who scheduled for open abdominal surgery lasting over 120 minutes underwent endotracheal intubation anesthesia, at the Department of Anesthesiology and Intensive Care, 108 Military Central Hospital, from February 2023 to February 2024. All patients were warmed using forced air warming devices and intravenous fluid warming devices. Results: The incidence of perioperative hypothermia (< 36°C) during anesthesia induction was 34%, with the majority (94.1%) experiencing mild hypothermia; 82.4% developed hypothermia within 1 hour after induction. The time to return to average body temperature in the recovery room was 35.5 ± 9.4 minutes, with a temperature recovery rate of 0.31°C every 30 minutes. Conclusion: The incidence of perioperative hypothermia in patients undergoing open abdominal surgery lasting over 120 minutes with endotracheal intubation anesthesia, using active warming devices, was 34%, with 94.1% experiencing mild hypothermia. The time to return to average body temperature in the recovery room was 35.5 ± 9.4 minutes postoperative.